2012
DOI: 10.1371/journal.pone.0043110
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Identification of CD44+/CD24− Cancer Cells in Primary Human Breast Carcinomas

Abstract: Breast cancer cells with the CD44+/CD24− phenotype have been reported to be tumourigenic due to their enhanced capacity for cancer development and their self-renewal potential. The identification of human tumourigenic breast cancer cells in surgical samples has recently received increased attention due to the implications for prognosis and treatment, although limitations exist in the interpretation of these studies. To better identify the CD44+/CD24− cells in routine surgical specimens, 56 primary breast carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
1
33
0
5
Order By: Relevance
“…Significantly shorter DFS in women with the CD44+/CD24- phenotype was reported in 4/9 studies, and is consistent with findings in this study (P=0.05). Notably, our study identified that the CD44+/CD24- phenotypes were significantly associated with TNBC (Table 2 and Table 3), which complement previous reports among other ethnic groups [26,27,34,36]. There is a plethora of data in the literature building a strong association of CD44+/CD24- with “cancer stem-cell (CSC) like” or “mesenchymal” phenotype [22,39-41].…”
Section: Discussionsupporting
confidence: 87%
“…Significantly shorter DFS in women with the CD44+/CD24- phenotype was reported in 4/9 studies, and is consistent with findings in this study (P=0.05). Notably, our study identified that the CD44+/CD24- phenotypes were significantly associated with TNBC (Table 2 and Table 3), which complement previous reports among other ethnic groups [26,27,34,36]. There is a plethora of data in the literature building a strong association of CD44+/CD24- with “cancer stem-cell (CSC) like” or “mesenchymal” phenotype [22,39-41].…”
Section: Discussionsupporting
confidence: 87%
“…The relative abundance of CD44 þ /CD24 À /low cells in BC has an average of 6.12%. 12 Thus, following tumor sample dissociation, cell suspensions were maintained in specific culture conditions that allowed the expansion of undifferentiated cancer stem and progenitor cells, while negatively selecting serumdependent tumor and non-transformed accessory cells. [13][14][15] These cell cultures were essentially composed of the so-called tumor 'mammospheres' (Figure 1a) formed by a majority of CD44 þ / CD24…”
Section: Introductionmentioning
confidence: 99%
“…ALDH1+ phenotype was found to be associated with biological aggressiveness and poor outcomes of breast cancer 9, 16, 17. Notably, several reports indicated that CD44 + /CD24 - and ALDH1+ breast cancer cells were associated with TNBC subtype 18-21. CD133, a transmembrane glycoprotein, is a more recent BCSC marker identified to be correlated with prognosis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%